Decision-Making and Risk Management in School Bullying Risk: Serial Mediation of Peer Relationships and Internet Addiction between Negative Parenting Styles and Adolescent Bullying - Huafeng Si; Dandan Zhang (Decision Making: Applications in Management and Engineering, 2025)
Understanding the underlying causes of school bullying is essential for developing effective prevention strategies. This study aims to investigate the impact of negative parenting styles on school bullying behaviors among adolescents, emphasizing the serial mediation role of peer relationships and internet addiction. In addition, the study frames school bullying as a decision-making and risk management challenge within organizational and governance contexts, highlighting how evidence-based models can guide sustainable operations management. A survey was administered to 756 randomly sampled students from junior and senior high schools in Henan, China. Assessment tools included the Parenting Styles Scale, Peer Relationships Scale, Internet Addiction Questionnaire, and School Bullying Behaviors Questionnaire. (1) Significant pairwise correlations were found between any two of the studied variables: negative parenting styles, peer relationships, internet addiction, and school bullying behavior. (2) Parental rejection and overprotection are two dimensions of negative parenting, and both were positive predictors of school bullying behaviors. (3) The impact of negative parenting styles on school bullying behaviors was mediated by three pathways: parental rejection → peer relationships → school bullying, parental overprotection → peer relationships → school bullying, and parental rejection → peer relationships → internet addiction → school bullying. Viewing bullying as an organizational risk, we map the mechanisms into a PDCA loop: identification via brief screeners to create risk profiles; intervention through parenting support, classroom‑climate routines, and tiered digital‑behavior programs; and evaluation using operational indicators (peer‑relationship means, ≥4 internet‑addiction proportion, bullying incidence). Digital‑behavior programs are prioritized when parental rejection is salient, whereas autonomy‑support and peer‑climate strengthening dominate under overprotection, with digital governance added only when peer deficits co‑occur with problematic use—thus enabling evidence‑based, socially sustainable school governance. Overall, the contribution of this study lies in integrating psychological, social, and behavioral insights into a structured decision-making framework, thereby advancing risk management and operations-management approaches for educational governance